Chronicle of Women: A Hongkong Story - Lilley, Rozanna (The Australian journal of anthropology, 1994)
In this paper I offer a feminist analysis of a theatrical production recently staged in Hongkong. I suggest that through a performative strategy of negotiating between compliance and resistance to normative constructions of Chinese/Hongkong womanhood, the show under consideration succeeds in giving us a highly nuanced representation of gendered colonial subjects. Many of these subtleties were erased by audience interpretations of the performance as an allegorical account of Hongkong/China relations framed by the issue of sovereignty transferral in 1997. Instead of seeing this as a negative process, I argue that critiques of patriarchy and political hegemony can and must productively interrupt one another in contemporary Hongkong.